A frequency reconfigurable filtering antenna based on stepped impedance resonator. Issue 5 (23rd March 2020) - Cui, Jingyu; Zhang, Anxue; Wu, Zixian; Yan, Sen
ABSTRACT: In this paper, a novel frequency reconfigurable filtering antenna is proposed for modern wireless communication systems. The feed network is composed of a stepped impedance resonator filter and a 50-Ω microstrip line. PIN diodes are used to switch the antenna to operate at either an ultra-wideband state or a dual-band state. For the dual-band state, the antenna operates at both 3.35 and 5.2 GHz. The measured results on tuning range, radiation patterns, and realized gains are provided, which show a good agreement with the numerical simulations.